Pengaruh Sanksi, Sosialisasi Tax Amnesty Dan Pemeriksaan Pajak Pada Keikutsertaan Tax Amnesty KPP Pratama Gianyar - Sayogaditya W. P. P., Tjokorda Gde Agung; Sukartha, I Made (E-Jurnal Akuntansi; Vol 28 No 2 (2019)DO - 10.24843/EJA.2019.v28.i02.p10, 2019)
The purpose of this study was to examine the effect of tax sanctions, socialization of tax  amnesty and tax audit on the participation of tax amnesty held by the Indonesian  government in 2016 at KPP Pratama Gianyar. Samples obtained using Nonprobability  Sampling, using the Slovin formula, obtained the number of 100 samples. The analytical  tool used is quantitative data analysis which includes multiple linear regression analysis  which is then processed with the help of SPSS. Based on the results, it is known that all  dependent variables have a positive effect on the participation of Tax Amnesty. Strict and  fair tax sanctions to taxpayers who violate will make taxpayers who are aware of  participating in tax amnesty to avoid penalties. Tax Amnesty socialization can increase  public knowledge about tax amnesty. With tax audits, taxpayers will take the initiative to  take part in tax amnesty, Keyword : Tax amnesty, sanctions, socialization.